Political ecology in/on/from Central America: a literature review - Gutiérrez Arguedas, Alberto (2023)
This paper aims to discuss the main theoretical, methodological and political issues in the field of political ecology (PE), from a Central American perspective. For this, it was carried out a search and systematization of existing academic literature in the field of PE, whose area of empirical study is located in Central America. From this search, a large volumen of publications (377) was collected, which were analyzed based on a set of key variables, emphasizing the relationships between knowledge, power and place of enunciation (who writes and from where). The results obtained reveal, among other things, a tension between the academic production elaborated on the region and that elaborated from the region.